Spitzer imaging of i '-drop galaxies: old stars at z approximate to 6 - Eyles, L; Bunker, A; Stanway, E; Lacy, M; Ellis, R; Doherty, M (2005)
We present new evidence for mature stellar populations with ages >100 Myr in massive galaxies (M stellar > 10 10 M ⊙) seen at a time when the Universe was less than 1 Gyr old. We analyse the prominent detections of two z ≈ 6 star-forming galaxies (SBM03#1 and #3) made at wavelengths corresponding to the rest-frame optical using the Infrared Array Camera camera onboard the Spitzer Space Telescope. We had previously identified these galaxies in Hubble Space Telescope (HST) Advanced Camera for Surveys (ACS) / Great Observatories Origins Deep Survey (GOODS) images of Chandra Deep Field South through the 'i′-drop' Lyman-break technique, and subsequently confirmed the identification spectroscopically with the Keck telescope. The new Spitzer photometry reveals significant Balmer/4000-Å discontinuities, indicative of dominant stellar populations with ages > 100 Myr. Fitting a range of population synthesis models (for normal initial mass functions) to the HST/Spitzer photometry yields ages of 250-650 Myr and implied formation redshifts z f ≈ 7.5-13.5 in presently-accepted world models. Remarkably, our sources have best-fitting stellar masses of 1.3-3.8 × 10 10 M ̇ (95 per cent confidence) assuming a Salpeter IMF. This indicates that at least some galaxies with stellar masses >20 per cent of those of a present-day L* galaxy had already assembled within the first Gyr after the Big Bang. We also deduce that the past average star formation rate must be comparable to the current observed rate (SFR UV ∼ 5-30 M ̇ yr -1), suggesting that there may have been more vigorous episodes of star formation in such systems at higher redshifts. Although a small sample, limited primarily by Spitzer's detection efficiency, our result lends support to the hypothesis advocated in our earlier analyses of the Ultra Deep Field and GOODS HST/ACS data. The presence of established systems at z ≈ 6 suggests that long-lived sources at earlier epochs (z > 7) played a key role in reionizing the Universe. © 2005 RAS.